2020
DOI: 10.1155/2020/5430407
|View full text |Cite
|
Sign up to set email alerts
|

Natural Drugs as a Treatment Strategy for Cardiovascular Disease through the Regulation of Oxidative Stress

Abstract: Oxidative stress (OS) refers to the physiological imbalance between oxidative and antioxidative processes leading to increased oxidation, which then results in the inflammatory infiltration of neutrophils, increased protease secretion, and the production of a large number of oxidative intermediates. Oxidative stress is considered an important factor in the pathogenesis of cardiovascular disease (CVD). At present, active components of Chinese herbal medicines (CHMs) have been widely used for the treatment of CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 203 publications
(195 reference statements)
2
48
0
Order By: Relevance
“…Many natural products of plants can protect endothelial cells by regulating mitochondrial function and reducing endothelial cell vulnerability under stress [ 56 , 57 ]. Our study directly confirmed the protective mechanism of natural antioxidants on endothelial cells through MQC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many natural products of plants can protect endothelial cells by regulating mitochondrial function and reducing endothelial cell vulnerability under stress [ 56 , 57 ]. Our study directly confirmed the protective mechanism of natural antioxidants on endothelial cells through MQC.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that Pue could regulate the mitophagy of endothelial cells and maintain normal cell activity. Autophagy/mitophagy not only controls the homeostasis of blood vessels but also functions in mitochondria energy metabolism and the mitochondrial antioxidant system to maintain the basic physiological functions of mitochondria [56,57]. Further research 9 Oxidative Medicine and Cellular Longevity is needed to determine the mechanistic interaction between autophagy/mitophagy and oxidative stress in the inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…Five compounds were identified by different extraction methods: ferulic acid, ginsenoside Rb1, astragaloside IV, diosgenin, and catalpol ( Figure 6 ). Studies have reported that the above five active ingredients from TYHX can play a good therapeutic effect in different types of cardiovascular diseases [ 20 , 23 ]. Moreover, it can protect many kinds of cells (including endothelial cells, cardiomyocytes, and sinoatrial node cells) under stress conditions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, strategies directed at a single target may be insufficient to ensure adequate protection [ 115 ]. Different natural bioactive compounds have thus far been described with pleiotropic beneficial effects on a plethora of CVD [ 116 ]. Among them, phenolic and terpenoid phytochemicals have been shown to protect the vascular and cardiac function against mitochondria-mediated pro-oxidant, pro-apoptotic, and pro-inflammatory injuries through the modulation of multiple cell signaling transduction pathways in different cell types [ 116 ].…”
Section: Mitochondria-targeting Of Natural Compounds With Pleiotromentioning
confidence: 99%
“…Different natural bioactive compounds have thus far been described with pleiotropic beneficial effects on a plethora of CVD [ 116 ]. Among them, phenolic and terpenoid phytochemicals have been shown to protect the vascular and cardiac function against mitochondria-mediated pro-oxidant, pro-apoptotic, and pro-inflammatory injuries through the modulation of multiple cell signaling transduction pathways in different cell types [ 116 ]. Thanks to their multitargeted effects and good tolerability, natural molecules are promising candidates to counteract the development of multifaceted disorders such as CVD ( Figure 5 ).…”
Section: Mitochondria-targeting Of Natural Compounds With Pleiotromentioning
confidence: 99%